(untitled) (Research, Society and Development, 2021)
Objective: to report the experience of building an application to help suspect common mental disorders, for users of the basic health network. Methodology: this is an experience report of the step-by-step construction of a technological prototype that aims to build a hybrid application, desktop and mobile, based on scales validated in Brazil. Results: the design of the application was designed in such a way that the steps of collecting information and answering the questionnaires were similar to a chat in real time. The final corrections and adjustments were carried out by means of functional tests and demands that arose during the elaboration, until the presentation of the final version. Conclusion: it is clear that the "MentalPro" application can be a useful tool, in environments such as waiting rooms, pre-service, nursing or medical consultations, and screening, assisting professionals and directing appropriate care to promote mental health. Is an open access product that proposes to adapt from use.